2009
DOI: 10.1051/0004-6361/200911696
|View full text |Cite
|
Sign up to set email alerts
|

The Hanle effect in a random magnetic field

Abstract: Context. The Hanle effect is used to determine weak turbulent magnetic fields in the solar atmosphere, usually assuming that the angular distribution is isotropic, the magnetic field strength constant, and that micro-turbulence holds, i.e. that the magnetic field correlation length is much less than a photon mean free path. Aims. To examine the sensitivity of turbulent magnetic field measurements to these assumptions, we study the dependence of Hanle effect on the magnetic field correlation length, its angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Two are of the accelerated lambda iteration (ALI) type; they are generalizations of the frequency-by-frequency (FBF) and core-wing methods originally formulated for scalar PRD transfer in Paletou & Auer (1995). The other is a scattering expansion (Neumann series) method developed for the Hanle effect with complete frequency redistribution in Frisch et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two are of the accelerated lambda iteration (ALI) type; they are generalizations of the frequency-by-frequency (FBF) and core-wing methods originally formulated for scalar PRD transfer in Paletou & Auer (1995). The other is a scattering expansion (Neumann series) method developed for the Hanle effect with complete frequency redistribution in Frisch et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…5, we show the convergence history for the ratio Q/I. We have not performed a systematic investigation of the variation in the speed of convergence with the slab thickness as was done for CRD in Frisch et al (2009), but the calculations that we have performed suggest that the behavior observed with CRD will also hold for angle-dependent and angle-averaged PRD, namely, a very good approximation to the emergent polarization is provided by the single scattered solution for optically thin slabs (T 10) and optically very thick ones (T ≥ 2 × 10 6 ), but is not reliable for intermediate optical thicknesses. As shown here, the problem can be cured by considering higher order terms in the scattering expansion.…”
Section: Validation and Convergence Properties Of The Iterative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Up to now, while many efforts have been devoted to the direct measurements of magnetic fields in the solar chromosphere and corona [e.g., Judge, 1998;Solanki et al, 2003;Lagg et al, 2004;Lin et al, 2004;Kramar et al, 2006;Trujillo Bueno and Asensio Ramos, 2007;Liu and Lin, 2008;Cargill, 2009;Frisch et al, 2009], the extrapolation based on NLFFF model is still a commonly used and necessary approach to understand the 3-D configuration of the coronal magnetic field. That is, the field can be reconstructed by solving the force-free and divergence-free differential equations (2) and (3) or equivalent equations (4) and (5), in which the observed photospheric vector magnetogram is taken as the bottom boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…In the following section we present an iterative method called the SEM to solve Eq. (11) efficiently (see Frisch et al 2009;Sampoorna et al 2011). …”
Section: A Decomposition Methods For Hanle Effect With Angle-dependentmentioning
confidence: 99%